Nanoparticle composite acrylic laminated board and preparation method thereof

By adding anti-aging agents, flame retardants and metal oxide nanoparticles to the acrylic laminate, the nanoparticle composite laminate is formed, which solves the problems of burning safety hazards and insufficient impact resistance of acrylic laminates, and achieves high hardness and resistance Improved wear, antibacterial and flame retardant properties, suitable for building decoration materials.

CN119116499AInactive Publication Date: 2024-12-13ZHEJIANG LIXINGDE TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411588008.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing acrylic laminates have problems of burn safety hazards and insufficient impact resistance in construction applications.

Method used

Nanoparticle composite acrylic laminate is used, including the middle PMMA layer and the upper and lower protective layer, and anti-aging agents, flame retardants, metal oxide nanoparticles, etc. are added, and the layered structure is formed through a high-pressure extruder to improve performance.

Benefits of technology

It has achieved improvements in high hardness, wear resistance, antibacterial, UV resistance and flame retardant properties, significantly improving the safety and service life of building materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119116499A_ABST
    Figure CN119116499A_ABST
Patent Text Reader

Abstract

The invention discloses a nano-particle composite acrylic laminated board and a preparation method thereof, and relates to the technical field of building materials. The laminated board comprises a middle PMMA layer and upper and lower protective layers; wherein the PMMA layer comprises an anti-aging agent and polymethyl methacrylate; the protective layer comprises an antioxidant, a flame retardant, metal oxide nanoparticles and polymethyl methacrylate. Compared with a traditional building material, firstly, the building material has the advantages of high mechanical strength, extremely high corrosion resistance, high surface hardness, wear resistance, durability and the like; the protective layer on the surface and the flame retardant are added, the service life of the product can be prolonged due to the added antioxidant component, the product is applied to indoor decoration building materials, the service life of wall materials can be greatly prolonged, and fire disasters and the like caused by high temperature of buildings can be effectively prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and more particularly to a nano-particle composite acrylic laminate and a preparation method thereof. Background Art

[0002] Acrylic is a chemical material, the chemical name is "PMMA" belongs to the polyacrylate class. Acrylic sheet is made of methyl methacrylate monomers, that is, polymethyl methacrylate sheet organic glass, also known as specially treated organic glass, is an alternative product of organic glass. In the application industry, the raw materials of acrylic generally appear in the form of sheets, etc. Due to its strong corrosion resistance, strong surface hardness and gloss, the application of acrylic sheet is becoming more and more extensive, especially in the fields of construction, advertising, etc. With the development and progress of society, more and more acrylic sheets are beginning to enter all walks of life.

[0003] (1) Since the limiting oxygen index of polymethyl methacrylate is only 17.3, acrylic laminates are very easy to burn in practical applications. If the relevant laminate materials are directly used as building materials for interior decoration, there will be great safety hazards. With the greater demand for material performance, there are greater safety hazards. The existing acrylic laminates have poor overall flame retardant effect, and there are certain safety hazards when used in buildings, which affects their use.

[0004] (2) In addition, although the existing acrylic laminates are hard, they are also very brittle, so their impact resistance has certain defects. If the relevant laminate materials are directly used as building materials for interior decoration, they are easily damaged during production and use.

[0005] Therefore, it is necessary to design and prepare a flame-retardant nanoparticle composite acrylic laminate. Summary of the invention

[0006] In view of this, the present invention provides a nanoparticle composite acrylic laminate and a preparation method thereof. The flame-retardant composite acrylic laminate provided by the present invention is mainly used in the construction field, especially in wall, ceiling, floor and other building decoration materials, which can prevent the building from being corroded and fire caused by high temperature. Compared with other existing polymer wall materials, the present invention not only has the advantages of high surface hardness, wear resistance, durability, etc., but also has flame retardant properties that can meet relevant requirements.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] A nanoparticle composite acrylic laminate, comprising a middle PMMA layer and upper and lower protective layers;

[0009] Wherein, the PMMA layer includes, by mass percentage: 0-0.04% of an anti-aging agent and the balance of polymethyl methacrylate;

[0010] The protective layer comprises, by mass percentage, 0.5-2% antioxidant, 3-5% flame retardant, 0.5-2% metal oxide nanoparticles, and the balance is polymethyl methacrylate.

[0011] Preferably, the anti-aging agent includes: UV-P.

[0012] Preferably, the flame retardant includes: brominated epoxy resin.

[0013] Preferably, the antioxidant includes: antioxidant 1076 or antioxidant 1010.

[0014] Preferably, the metal oxide nanoparticles include: niobium pentoxide, cerium dioxide or titanium dioxide whose surface is treated with hexadecyltrimethylammonium bromide or hexadecyltrimethylammonium chloride.

[0015] Since the protective layer is compounded with semiconductor nanomaterials such as niobium pentoxide and cerium dioxide, and the related additives have anti-ultraviolet and antibacterial components, the present invention can achieve certain anti-ultraviolet and antibacterial properties, meet the relevant practical use requirements, and achieve a certain mechanical performance improvement effect. The addition of semiconductor nanomaterials achieves the comprehensive effect of anti-ultraviolet, antibacterial and mechanical performance improvement. The layered structure is prepared by a co-extrusion method, which is simple and suitable for large-scale production.

[0016] Another object of the present invention is to provide a method for preparing the above-mentioned nanoparticle composite acrylic laminate, comprising the following steps:

[0017] (1) Adding polymethyl methacrylate particles into a screw and heating them to a molten state, then adding an anti-aging agent and dispersing it evenly, and after cooling, using a high-pressure extruder to extrude the PMMA layer surface to obtain a PMMA layer;

[0018] (2) The polymethyl methacrylate particles are heated to a molten state, and during the heating process, flame retardants, antioxidants, and metal oxide nanoparticles are added and mixed, and mechanical stirring is maintained to make them evenly dispersed. After cooling, a high-pressure extruder is used to extrude and mold the PMMA layer surface to obtain a composite acrylic laminate.

[0019] Preferably, the thickness of the PMMA layer is 1.5-2.5 mm.

[0020] Preferably, the thickness of the protective layer is 0.1-0.3 mm.

[0021] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0022] Due to the introduction of relevant niobium pentoxide or other nanoparticles, the comprehensive performance of antibacterial, anti-ultraviolet and mechanical properties has been successfully improved, which has the advantages of low cost and the ability to improve multiple comprehensive properties at the same time. Compared with traditional building materials, first of all, it has the advantages of high mechanical strength, strong corrosion resistance, high surface hardness, wear resistance, and durability; and the surface protective layer and the addition of flame retardants make it flame retardant, and the added antioxidant ingredients can extend the service life of related products. The relevant laminate products are used in interior decoration building materials, which can greatly increase the service life of wall materials and effectively prevent fires caused by high temperatures in buildings. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0024] Figure 1 This is a structural diagram of the laminate of the present invention;

[0025] Figure 2 It is a friction coefficient comparison chart, wherein the left picture is comparative example 1, and the right picture is embodiment 1. DETAILED DESCRIPTION

[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] See also Figure 1 , Example 1 discloses the flame-retardant acrylic laminate environmentally friendly building material described in the present invention, including a middle PMMA layer and upper and lower protective layers;

[0029] The PMMA layer is recorded by mass percentage, including: UV-P 0.04%, brominated epoxy resin 5%, and the balance is polymethyl methacrylate;

[0030] The protective layer includes, by mass percentage, 2% antioxidant 1076, 5% brominated epoxy resin, 2% niobium pentoxide whose surface is treated with hexadecyltrimethylammonium chloride, and the balance is polymethyl methacrylate.

[0031] The preparation method comprises: (1) adding polymethyl methacrylate particles into a screw and heating them to a molten state, then adding an anti-aging agent and dispersing the anti-aging agent uniformly, and after cooling, extruding the PMMA layer surface using a high-pressure extruder to obtain a PMMA layer;

[0032] (2) The polymethyl methacrylate particles are heated to a molten state, and during the heating process, flame retardants, antioxidants, and metal oxide nanoparticles are added and mixed, and mechanical stirring is maintained to make them evenly dispersed. After cooling, a high-pressure extruder is used to extrude and mold the PMMA layer surface to obtain a composite acrylic laminate.

[0033] Example 2

[0034] See also Figure 1 , Example 2 discloses the flame-retardant acrylic laminate environmentally friendly building material described in the present invention, including a middle PMMA layer and upper and lower protective layers;

[0035] Wherein, the PMMA layer is recorded by mass percentage and includes: polymethyl methacrylate;

[0036] The protective layer includes, by mass percentage, 0.5% antioxidant 1010, 3% brominated epoxy resin, 0.5% titanium dioxide with the surface treated with hexadecyltrimethylammonium bromide, and the balance polymethyl methacrylate.

[0037] The preparation method comprises: (1) adding polymethyl methacrylate particles into a screw and heating them to a molten state, maintaining mechanical stirring to make them dispersed evenly, and after cooling, using a high-pressure extruder to extrude and mold on the surface of the PMMA layer to obtain a PMMA layer;

[0038] (2) The polymethyl methacrylate particles are heated to a molten state, and during the heating process, flame retardants, antioxidants, and metal oxide nanoparticles are added and mixed, and mechanical stirring is maintained to make them evenly dispersed. After cooling, a high-pressure extruder is used to extrude and mold the PMMA layer surface to obtain a composite acrylic laminate.

[0039] Example 3

[0040] See also Figure 1 , Example 1 discloses the flame-retardant acrylic laminate environmentally friendly building material described in the present invention, including a middle PMMA layer and upper and lower protective layers;

[0041] The PMMA layer is recorded by weight percentage, including: UV-P 0.01%, brominated epoxy resin 4%, and the balance is polymethyl methacrylate;

[0042] The protective layer includes, by mass percentage, 1% antioxidant 1010, 4% brominated epoxy resin, 1% cerium dioxide with the surface treated with hexadecyltrimethylammonium chloride, and the remainder polymethyl methacrylate.

[0043] The preparation method comprises: (1) adding polymethyl methacrylate particles into a screw and heating them to a molten state, then adding an anti-aging agent and dispersing the anti-aging agent uniformly, and after cooling, extruding the PMMA layer surface using a high-pressure extruder to obtain a PMMA layer;

[0044] (2) The polymethyl methacrylate particles are heated to a molten state, and during the heating process, flame retardants, antioxidants, and metal oxide nanoparticles are added and mixed, and mechanical stirring is maintained to make them evenly dispersed. After cooling, a high-pressure extruder is used to extrude and mold the PMMA layer surface to obtain a composite acrylic laminate.

[0045] Comparative Example 1

[0046] Comparative Example 1 is a control group ordinary PMMA laminate, the main material of which is PMMA, and its specific structure includes Figure 1 The PMMA layer in the embodiment of the present invention does not include the protective layer.

[0047] Hardness test

[0048] The microhardness was measured using a Vickers hardness tester with a load of 10 g and a dwell time of 15 s. The average value of 5 locations was selected to determine the microhardness value of each sample.

[0049] After measurement, the calculated hardness of comparative example 1 is 52.12 HV0.01, and the calculated hardness of embodiment 1 is 60.78 HV0.01. It can be seen that the hardness is significantly improved after treatment.

[0050] Wear test

[0051] The samples were subjected to dry sliding wear tests using a high-speed reciprocating friction and wear tester. Under a load of 10 N, the samples were rubbed with a GCr15 grinding ball with a diameter of 6 mm at a sliding speed of 500 t / min for 30 min, and the wear track length was kept at 5 mm. Then, the profile of the wear track was obtained using a surface profiler. The value of the wear volume (V) was obtained by the following formula:

[0052] V = S l

[0053] Where l is the length of the wear track (5 mm), and S is the area adjacent to the wear track under the initial surface, which can be obtained from the cross section of the wear track. The wear rate (K) can be calculated by the formula:

[0054] K=V / (F·L)

[0055] Where F is the normal load (10 N) and L is the total sliding length (150 m).

[0056] Figure 2 The left figure is comparative example 1, and the calculated wear rate k = 3.5×10 -4 mm 3 / Nm, the right figure is Example 1, the calculated wear rate k = 4.5×10 -4 mm 3 / Nm. It can be seen that the friction coefficient decreases after treatment.

[0057] Flame retardant test:

[0058] Relevant tests were conducted according to the fire protection level UL94. After testing, ordinary PMMA laminates with untreated surfaces continued to burn after ignition and did not have flame retardant properties. PMMA products with treated surfaces and containing a specific protective layer were tested to have a horizontal burning rate of HB grade flame retardant effects after ignition, which was significantly improved compared to ordinary products with untreated surfaces.

[0059] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

[0060] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A nanoparticle composite acrylic laminate, characterized in that: Including the middle PMMA layer and upper and lower protective layers; Wherein, the PMMA layer comprises, by mass percentage, 0-0.04% of an anti-aging agent and the balance of polymethyl methacrylate; The protective layer comprises, by mass percentage, 0.5-2% of an antioxidant, 3-5% of a flame retardant, 0.5-2% of metal oxide nanoparticles, and the balance being polymethyl methacrylate.

2. The nanoparticle composite acrylic laminate according to claim 1, characterized in that: The anti-aging agent includes: UV-P.

3. The nanoparticle composite acrylic laminate according to claim 1, characterized in that: The flame retardant includes brominated epoxy resin.

4. The nanoparticle composite acrylic laminate according to claim 1, characterized in that: The antioxidant includes: antioxidant 1076 or antioxidant 1010.

5. The nanoparticle composite acrylic laminate according to claim 1, characterized in that: The metal oxide nanoparticles include: niobium pentoxide, cerium dioxide or titanium dioxide, the surface of which is treated with hexadecyltrimethylammonium bromide or hexadecyltrimethylammonium chloride.

6. A method for preparing the nanoparticle composite acrylic laminate according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Add polymethyl methacrylate particles into the screw and heat them to a molten state, then add an anti-aging agent and disperse it evenly, and after cooling, use a high-pressure extruder to extrude it on the surface of the PMMA layer to obtain a PMMA layer; (2) Heat the polymethyl methacrylate particles to a molten state, add flame retardants, antioxidants, and metal oxide nanoparticles during the heating process, and keep mechanical stirring to make them evenly dispersed. After cooling, use a high-pressure extruder to extrude and mold on the surface of the PMMA layer to obtain a composite acrylic laminate.

7. The method for preparing a nanoparticle composite acrylic laminate according to claim 6, characterized in that: The thickness of the PMMA layer is 1.5-2.5 mm.

8. The method for preparing a nanoparticle composite acrylic laminate according to claim 7, characterized in that: The thickness of the protective layer is 0.1-0.3 mm.

Citation Information

Patent Citations

  • Co-extruded composite board for tabletop and preparation method for co-extruded composite board

    CN103802425A

  • Antibacterial acrylic plate as well as preparation method and application thereof

    CN115972721A

  • Non-release composite antibacterial material, antibacterial fabric and preparation method thereof

    CN117364483A

  • High-performance polylactic acid composite material as well as preparation method and application thereof

    CN118562266A

  • High-strength waterproof acrylic plate and preparation process thereof

    CN118745275A